Economic history = Hospodářské dějiny Published on the occasion of the VIIth International Economic History Congress in Edinburg 1978 (Institute of Czechoslovak Academy of Sciences, 1978)
Long-term radial extension of the growth pole effect in the Prague suburban aerea 1869-1970 : Contour diagram : Appendix to O. Bartušek's treatise.